2023
DOI: 10.3390/v15091954
|View full text |Cite
|
Sign up to set email alerts
|

When Bacteria and Viruses Collide: A Tale of Chlamydia trachomatis and Sexually Transmitted Viruses

Ehsan Ghasemian,
Emma Harding-Esch,
David Mabey
et al.

Abstract: The global incidence of sexually transmitted infections (STIs) remains high, with the World Health Organization (WHO) estimating that over 1 million people acquire STIs daily. STIs can lead to infertility, pregnancy complications, and cancers. Co-infections with multiple pathogens are prevalent among individuals with an STI and can lead to heightened infectivity and more severe clinical manifestations. Chlamydia trachomatis (CT) is the most reported bacterial STI worldwide in both men and women, and several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 175 publications
(348 reference statements)
0
1
0
Order By: Relevance
“…Trachoma is a blinding disease caused by repeated infection of the eyes with Chlamydia trachomatis (Ct) serovar (Sv) A, B, Ba and C [1,2]. Ct is the leading cause of bacterial sexually transmitted infections globally [3,4]. In 1998, the World Health Organisation (WHO) introduced the SAFE strategy to eliminate trachoma as a public health problem by 2020 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Trachoma is a blinding disease caused by repeated infection of the eyes with Chlamydia trachomatis (Ct) serovar (Sv) A, B, Ba and C [1,2]. Ct is the leading cause of bacterial sexually transmitted infections globally [3,4]. In 1998, the World Health Organisation (WHO) introduced the SAFE strategy to eliminate trachoma as a public health problem by 2020 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the WHO (World Health Organization) has reported that over one million people contract sexually transmitted infections daily [7]. Thus, Ct is far from being eliminated unless a sexual strategy is implemented in the SAFE program.…”
mentioning
confidence: 99%